PENGARUH MODEL PEMBELAJARAN AKTIF TIPE CARD SORT DAN MOTIVASI BELAJAR DALAM MATA KULIAH KETERAMPILAN BERSASTRA KE-SD-AN MAHASISWA PRODI PGSD - Hidayati Azkiya (Universitas Ahmad Dahlan, 2017)
This study begins from the problem of low skills learning ability to compose Elementary literature in PGSD departement of Bung Hatta University. It can be seen from the results of students’ mid semester test, observation, and interviews with faculty to compose literature Skills in elementary course. This study aims to determine the effect of the application of an active learning model type of card sort to compose skills to elementary school's student in PGSD Department and to know the results of learning skills to compose an Elementary course-students after being taught by active learning model type of card sort. This type of research was a Quasi Experimental study. The populations were all students in PGSD department Academic Year 2015/2016.The Data collection techniques in this study used questionnaires of learning motivation and learning skills tests to compose Elementary literature in PGSD. The Data analysis techniques used in this study were t-test and ANOVA. Based on the findings, we concluded that first learning skills to compose elementary literature students who use active learning model type of card sort was higher than in convenetional than students who used conventional learning either seen as a whole or from high and low learning motivation. Second, there was no interaction between the learning motivation to learn the skills of learning to compose Elementary literature of PGSD students. It means that active learning model type of card sort gave good effect on learning skilss to compose Elementary literature of PGSD students.